Dobrovolnictví v kontextu životní dráhy dobrovolníků - Pospíšilová, Tereza (Lidé města, 2010)
Volunteering is a topic that is so far neglected within the Czech academic community. The article focuses on formal volunteering. Based on a review of volunteering literature, we pose the question whether the meaning and experiences of volunteering relate to the life stages of volunteers; emphasis is placed on the relation of volunteering to employment. The research is based on interpretative paradigm and qualitative research methodology. Based on semi-structured interviews, we show that volunteering relates to the course of life and employment in a crucial way. The key category is leisure time, in which volunteering takes place and which is in interviews portrayed in tension with time devoted to necessary duties (such as work and care for small children). Voluntary activity is defined by volunteers as a leisure-time (free time) activity and as above their obligatory duties. Thus, volunteering is neither a simple outcome of specific motivations or values, nor the result of some objective state (such as a certain number of hours per week away from work or childcare). In conclusion, we present a pilot conceptual scheme for the future research of volunteering in the context of the life course of volunteers.